2017
DOI: 10.1002/ps.4638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pyriproxyfen on wild populations of the housefly, Musca domestica, and compatibility with its principal parasitoids

Abstract: PPF is still an effective tool for housefly control, but resistance management practices should be employed to avoid resistance. PPF is compatible with principal housefly parasitoids at concentrations <600 mg kg , and is suitable for use in integrated pest management. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 38 publications
2
10
0
3
Order By: Relevance
“…The difference between the results of the two exposure methods is likely due to a longer exposure time of 5-10 min in the treated tube apparatus compared with 3 min in the Petri dish, which resulted in a higher amount of PPF acquired in the tubes. These results corroborate previous research (Geden and Devine 2012;Biale et al 2017) about the effectiveness of PPF for controlling house flies, at least under laboratory conditions. Our results suggest that treated flies retain enough dust to treat oviposition sites on the day of Table 4 Effect of varying the proportion of PPF-treated (by forced contact) female house flies on pupal mortality, after flies were placed on wheat bran rearing medium or different animal manures for 24 h after exposure.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The difference between the results of the two exposure methods is likely due to a longer exposure time of 5-10 min in the treated tube apparatus compared with 3 min in the Petri dish, which resulted in a higher amount of PPF acquired in the tubes. These results corroborate previous research (Geden and Devine 2012;Biale et al 2017) about the effectiveness of PPF for controlling house flies, at least under laboratory conditions. Our results suggest that treated flies retain enough dust to treat oviposition sites on the day of Table 4 Effect of varying the proportion of PPF-treated (by forced contact) female house flies on pupal mortality, after flies were placed on wheat bran rearing medium or different animal manures for 24 h after exposure.…”
Section: Discussionsupporting
confidence: 92%
“…In No. of treated females a previous study, we found that this range of concentrations resulted in 100% pupal mortality when applied directly to the substrate (Biale et al 2017). Curiously, tests with Israeli manure and flies indicated relatively poor performance on cow manure, and results with USA manure and flies showed lower efficacy on horse manure.…”
Section: Substratementioning
confidence: 51%
See 2 more Smart Citations
“…It disrupts the hormonal system of the insects interfering with their development and transformation into adults [4]. Pyriproxyfen is used for controlling household pests such as the German cockroach (Blattella germanica) [5] and the common housefly (Musca domestica) [6] as well as for prophylactic flea control on cats and dogs [7,8]. Pyriproxyfen is particularly efficacious as larvicide against all the mosquito species [9][10][11].…”
Section: Introductionmentioning
confidence: 99%